Anticancer effect of Triphala extract on the hepatocellular carcinoma cells in mice - Jantana Yahuafai; Prayumat Onsrisawat; Suratsawadee Piyaviriyakul; Jannarin Nontakham; Naowarat Suthamnatpong (GarVal Editorial Ltda., 2023)
Context: Triphala is a traditional herbal formulation consisting of dried fruits from three plants namely, Terminalia bellirica, Terminalia chebula and Phyllanthus emblica. Its traditional used to treat many ailments, including various types of cancers, health promotion, and longevity. Aims: To evaluate the ability of an aqueous extract Triphala (TPL) to inhibit the growth of Hepatocellular carcinoma cells (HepG2) and in mice. Methods: The anticancer activity of TPL and its composite extracts was assessed in vitro by MTT assay with HepG2 cells. The mice were inoculated with HepG2 cells and then divided randomly into six groups (6 mice/group): control group, positive control group (intraperitoneal with 3 mg/kg body weight doxorubicin), and TPL treatment groups (oral administrated with 50, 100, and 200 mg/kg body weight TPL, respectively). Anticancer activity based on body weight, tumor growth volumes, survival time, relative organ weight, and hematological parameters was determined after administrating the TPL for 14 consecutive days. Results: The results demonstrated that the TPL extract exhibited antiproliferative activity against HepG2 cells in a time-dependent manner of treatment. The selectivity index (SI) showed that TPL is highly selective (SI>3) against the HepG2 cell line and has no activity against non-tumor cells.Oral administration with TPL extract at the dose of 200 mg/kg body weight inhibited tumor growth volume and increase the survival time. No abnormality of hematological parameters, relative organ weight, body weight, and morphology of organs were observed. Conclusions: The TPL extract at the test doses was a non-toxic drug. Our finding reveals the anticancer efficacy of TPL extract.